2016
DOI: 10.1007/s00268-016-3603-1
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia/Muscle Mass is not a Prognostic Factor for Short‐ and Long‐Term Outcome After Esophagectomy for Cancer

Abstract: BackgroundRecent studies have suggested that sarcopenia is a prognostic risk indicator of postoperative complications and predicts survival in cancer patients. The aim of this study is to investigate whether sarcopenia is associated with postoperative short-term outcome (morbidity and mortality) and long-term survival in patients undergoing esophagectomy for cancer after neoadjuvant chemoradiotherapy.MethodsAll patients who underwent neoadjuvant chemoradiotherapy followed by esophagectomy for cancer, and of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
2
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(84 citation statements)
references
References 27 publications
6
72
2
2
Order By: Relevance
“…A large number of studies evaluated the role of sarcopenia on survival outcomes after esophagectomy. In spite of some studies suggesting that sarcopenia had no impact on OS, [47][48][49] a recent meta-analysis 15 showed that sarcopenia is in fact an unfavorable prognostic factor. In contrast, sarcopenia in metastatic esophageal carcinoma setting was not associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies evaluated the role of sarcopenia on survival outcomes after esophagectomy. In spite of some studies suggesting that sarcopenia had no impact on OS, [47][48][49] a recent meta-analysis 15 showed that sarcopenia is in fact an unfavorable prognostic factor. In contrast, sarcopenia in metastatic esophageal carcinoma setting was not associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Current literature on the influence of body composition parameters [including body mass index (BMI), body fat percentage, skeletal muscle index, and sarcopenia] on post‐operative morbidity and long‐term survival in patients with oesophageal cancer after curative intent treatment is scarce, and literature on sarcopenia is often contradictory. Some studies show that sarcopenia is an independent predictor for development of post‐operative complications and overall and disease‐free survival while other studies did not find any correlation . Few studies take other factors such as muscle strength and fat percentage or fat distribution into consideration.…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been some reports that perioperative skeletal muscle loss was a prognostic predictor after surgeries for cancers including ESCC (8)(9)(10)(11)(12)(13)(14)30), they examined skeletal muscle loss in the preoperative phase or the postoperative chronic phase (about 1 or more months after surgery). Surprisingly, in the present study, the TPI reduction rate on POD 3 after ESCC surgery was an independent long-term predictor of prognosis that was as signi cant as pathological stage and neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%